First-line treatment in advanced or metastatic disease: one size fits all or adapted to specific histiotypes?. Issue 4 (July 2016) - Seddon, Beatrice
Abstract : Purpose of review: This article evaluates the supporting evidence for adapting choice of first-line chemotherapy to specific histological subtypes in advanced or metastatic soft tissue sarcoma (STS). Recent findings: The evidence for the current standard of care for first-line chemotherapy in STS is reviewed. This is followed by an overview of the evidence for use of specific chemotherapy drugs in a number of specific STS histological subtypes. The more recent literature on newer drugs being used in the first-line setting in STS is then reviewed, and finally an assessment is made as to whether it is possible at this time to tailor first-line chemotherapy to histiotype. Summary: The review shows that at present there is insufficient evidence to support the concept of adapting choice of first-line chemotherapy in advanced or metastatic STS to specific histiotypes.